Local Star-forming Galaxies Build Up Central Mass Concentration Most Actively near M ∗ = 1010 M ⊙ - Zhizheng Pan; Xianzhong Zheng; Xu Kong (The Astrophysical Journal, 2023)
To understand in what mass regime star-forming galaxies (SFGs) build up central mass concentration most actively, we present a study on the luminosity-weighted stellar age radial gradient (∇ _age ) distribution of ∼3600 low-redshift SFGs using the MaNGA Pipe3D data available in Data Release 17 from the Sloan Digital Sky Survey. The mean age gradient is negative, with ∇ _age = −0.14 log Gyr/ R _e , consistent with the inside-out disk formation scenario. Specifically, SFGs with positive ∇ _age consist of ∼28% at log ( M _* / M _⊙ ) < 9.5, while this fraction rises up to its peak (∼40%) near log ( M _* / M _⊙ ) = 10 and then decreases to ∼15% at log ( M _* / M _⊙ ) = 11. At fixed M _* , SFGs with positive ∇ _age typically have more compact sizes and more centrally concentrated star formation than their counterparts, indicative of recent central mass buildup events. These results suggest that the buildup of central stellar mass concentration in local SFGs is mostly active near M _* = 10 ^10 M _⊙ . Our findings provide new insights into the origin of morphological differences between low-mass and high-mass SFGs.